European Pediatric Surgeon' Association Survey on the Management of Short-Bowel Syndrome - Dariel, Anne; Faure, Alice; Martinez, Leopoldo; Morini, Francesco; Pini Prato, Alessio; Friedmacher, Florian; Coste, Marie-Edith (European Journal of Pediatric Surgery, 2020)
Introduction The aim of this study was to assess the management of short-bowel syndrome (SBS) at the time of primary surgery, and the strategies used to facilitate enteral autonomy depending on the institutional expertise.Materials and Methods An online questionnaire was sent in 2019 to members of The European Pediatric Surgeons' Association.Results Among the 65 responding members (26 countries, 85% from university hospitals), 57% manage less than three new patients with SBS per year (group A), and 43% at least three patients (group B). The cut-off of three patients treated yearly used in our study was defined after statistical analysis of different cut-offs. A multidisciplinary intestinal rehabilitation program is significantly more frequent in group B than in group A (85 and 53%, respectively; p = 0.009). Considering the primary surgical management of multiple intestinal atresia and congenital ultra-short bowel with jejunal atresia, primary surgical strategies to optimize bowel length are more often used in group B than group A (p = 0.09 and p = 0.04, respectively). A minimum of one intestinal lengthening procedure every 2 to 3 years is significantly more frequent in group B than group A (95 and 45%, respectively; p = 0.0013). Among the strategies used to promote intestinal adaptation, group B (35%) uses significantly more often glucagon-like peptide 2 analogs than group A (10%) (p = 0.02).Conclusion Based on our survey, a minimum number of SBS patients treated yearly is required to manage this challenging disease according to up-to-date medical and surgical strategies. However, whatever their level of expertise is in managing SBS, most of pediatric surgeons are involved in the primary surgery. Medical education programs about SBS should be more largely available to pediatric surgeons.
Keywords: short-bowel syndrome; surgery; multidisciplinary; intestinal adaptation; secondary serial transverse enteroplasty